Progressive Poling of Large Area, High r33 Electro-Optic Polymer SEO100c - Michael Maurer; Evan Gawron; Christopher Middlebrook (Applied Sciences, 2021)
SEO100c, an EO-polymer, has been reported of having an r33 in excess of 100 pm/V. Experimental poling research was performed on rib waveguide modulator for device design and development. Reported is the determination of the impact that temperature and voltage have on the poling of a SEO100c waveguide device in order to maximize the r33 while avoiding damage to the device structure ensuring high yield in manufacture. The poling process is shown to have a nonlinear relationship between r33 and poling field aiding in the selection of achievable poling voltages for required r33 values. Device thermal stability is quantified and reported for the complete poling process and the impacts upon r33. Investigation into the possible relaxation of device r33 is measured over an extended period demonstrating desirable use within deployable devices.